Abdominal hernia repair composite patch and preparation method thereof
By designing a multi-layer structure of abdominal wall hernia repair composite patch, the combination of support layer, anti-adhesion layer and inducing layer is used to solve the problem of materials in the prior art that cannot degrade, absorb and lack of regeneration ability, and achieve efficient hernia repair and promoting tissue regeneration.
Patent Information
- Application Number
- CN202510584985.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-06-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing abdominal wall hernia patch materials cannot be degraded and absorbed, resulting in foreign body reaction; while the absorbable biological patches lack the ability to promote abdominal wall regeneration, resulting in repair failure and high recurrence rates.
A composite patch for abdominal wall hernia repair was designed, and a multi-layer structure of support layer, anti-adhesion layer and inducing layer was prepared by electrospinning process. The anti-adhesion layer prevents the patch from adhesion to surrounding tissues, and the inducing layer uses bioactive materials to promote tissue regeneration.
It significantly improves the success rate of hernia repair, reduces postoperative complications, promotes the patient's postoperative quality of life, and reduces the recurrence rate.
Smart Images

Figure CN120078549A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of biological medicine technology, and particularly to an abdominal wall hernia repair composite patch and a preparation method thereof. Background Art
[0002] Hernia is a general surgical disease with a high incidence rate and can only be treated by tension-free hernia repair surgery. The treatment method of using a hernia repair patch to repair the hernia ring opening greatly reduces the pain of patients and the recurrence of hernia. However, most commercial patch materials cannot be degraded and absorbed, which will cause foreign body reactions in patients. At the same time, absorbable biological patches lack the ability to promote abdominal wall regeneration, ultimately leading to failed repair at the defect site and a high recurrence rate. Therefore, there is an urgent need to develop new patch products to meet clinical and market demands. Summary of the Invention
[0003] In order to improve the problem of failed repair caused by the lack of the ability of absorbable biological patches to promote abdominal wall regeneration, this application provides an abdominal wall hernia repair composite patch and a preparation method thereof.
[0004] In the first aspect, this application provides an abdominal wall hernia repair composite patch, adopting the following technical solution: An abdominal wall hernia repair composite patch, comprising: a support layer, an anti-adhesion layer, and an induction layer. The anti-adhesion layer and the induction layer are respectively arranged on the same side of the support layer, and the minimum linear distance between the anti-adhesion layer and the induction layer is 0 - 10 mm.
[0005] Optionally, the length of the support layer is 12 - 20 cm, and the width is 10 - 15 cm.
[0006] This application realizes a comprehensive optimization of the hernia repair effect through a unique multi-layer structure design. First of all, the support layer ensures the high strength and stability of the patch, providing a solid support for the repair area. The anti-adhesion layer and the induction layer are closely adjacent but do not interfere with each other. The precise control of the minimum linear distance not only avoids the overlap and waste of materials but also ensures the full play of their respective functions. The anti-adhesion layer effectively prevents the adhesion of the patch to the surrounding tissues, reducing the occurrence of postoperative complications; while the induction layer uses bioactive materials to promote tissue regeneration and accelerate the healing process. This comprehensive design significantly improves the success rate of hernia repair and the postoperative quality of life of patients.
[0007] Specifically, setting the minimum linear distance between the anti-adhesion layer and the induction layer is to define the relationship that the anti-adhesion layer and the induction layer are closely connected, and a gap not exceeding 10 mm is also allowed, so as to maximize the layout of the anti-adhesion layer and the induction layer.
[0008] In the solution of this application, the shape of the composite patch is not limited and can be rectangular, square, circular, etc.
[0009] Optionally, two pieces of the induction layer are provided and are respectively located on both sides of the anti-adhesion layer.
[0010] Furthermore, the length of each piece of the induction layer is equal to the length of the support layer, and the width of each piece of the induction layer accounts for 10%-15% of the width of the support layer.
[0011] In a preferred embodiment of the present application, the two pieces of the induction layer have exactly the same size and are symmetrically arranged on both sides in the width direction of the anti-adhesion layer, so that the induction layers on both sides of the anti-adhesion layer can fully contact the skin around the hernia orifice, and exert their ability to promote cell growth and tissue repair.
[0012] Through such a structural design of the present application, the induction layer can contact most of the skin or tissues around the hernia orifice, which is more conducive to promoting cell regeneration and repair in a larger range. Moreover, the anti-adhesion layer is arranged between the two pieces of the induction layer, and the two do not interfere with each other, do not affect the exertion of their respective functions, and at the same time do not increase the overall thickness of the patch, reducing the foreign body sensation and discomfort of the patient when using the patch, and at the same time reducing the difficulty during the operation.
[0013] Optionally, the induction layer is in a zigzag structure, and the anti-adhesion layer is located inside the induction layer.
[0014] Furthermore, the outer edge of the induction layer is flush with the outer edge of the support layer, and the width difference between the inner and outer edges of the induction layer is 10%-15% of the size of the outer edge of the induction layer.
[0015] By designing the induction layer into a zigzag structure in the present application, this special shape helps to guide the directional growth of the surrounding tissues and promotes good combination with the patch. At the same time, the zigzag structure also provides enough space for the anti-adhesion layer to ensure that it can play the role of anti-adhesion.
[0016] Moreover, the zigzag structure of the induction layer can contact all the skin around the hernia orifice, maximizing its ability to promote cell growth and tissue repair, and at the same time not affecting the anti-adhesion layer from playing its anti-adhesion role.
[0017] It should be noted that when the shape of the composite patch is rectangular, the width differences between the inner and outer edges of the induction layer located on the long side do not have to be equal, and can be specifically limited according to the size of the side where it is located, that is, the width difference between the inner and outer edges of the induction layer located on the long side is 10%-15% of the long side of the support layer, and the width difference between the inner and outer edges of the induction layer located on the short side is 10%-15% of the short side of the support layer.
[0018] Optionally, the thickness of the support layer is 0.2 - 0.45 mm, the thickness of the anti-adhesion layer is 0.15 - 0.35 mm, and the thickness of the induction layer is 0.1 - 0.25 mm.
[0019] By defining the thickness of each layer of the hernia repair composite patch and its laminate structure, the present application controls the thickness of the entire hernia repair composite patch within 0.8 mm. After the patch is implanted into the body, the foreign body sensation of the patient is relatively small. This helps to improve the comfort of the patient and may reduce the discomfort caused by the presence of the patch. In addition, the thinner patch has a lower shrinkage rate, which helps to maintain the stability and shape of the patch.
[0020] In a preferred embodiment, the thickness of the support layer is 0.25 - 0.4 mm, the thickness of the anti-adhesion layer is 0.2 - 0.3 mm, and the thickness of the induction layer is 0.15 - 0.2 mm.
[0021] By further defining the thickness of each functional layer of the composite patch, especially by designing the thickness of the induction layer to be thinner than that of the anti-adhesion layer, the obstacles to cell migration and growth are reduced, making it easier for cells to contact and bind to the patch material, which is more conducive to the rapid ingrowth and attachment of surrounding tissue cells, thereby accelerating the healing process of the repair site. In addition, the thinner induction layer makes the patch material smoother, reducing the friction and interaction with the surrounding tissue, so it can also achieve the purpose of reducing the risk of adhesion.
[0022] Optionally, the raw materials for preparing the support layer include PLLA-CL with a number average molecular weight of 80,000 - 110,000, the raw materials for preparing the anti-adhesion layer include PLA with a number average molecular weight of 80,000 - 110,000, and the raw materials for preparing the induction layer include one or more of gelatin, silk fibroin, and hyaluronic acid.
[0023] The support layer of the present application uses PLLA-CL with a number average molecular weight of 80,000 - 110,000 as the raw material. This material not only has excellent mechanical strength and stability but also good biocompatibility, which can provide strong support for the repair area and ensure the persistence and stability of the patch in the body. The anti-adhesion layer selects PLA material with the same molecular weight range. Its smooth surface and low reactivity effectively prevent the adhesion of the patch to the surrounding tissue, greatly reducing the risk of postoperative complications. At the same time, the degradability of PLA also ensures that it can be gradually absorbed by the body after completing the anti-adhesion task, avoiding long-term foreign body stimulation. The induction layer mimics the components of the extracellular matrix and focuses on promoting tissue regeneration, inducing the ingrowth and proliferation of body cells.
[0024] Optionally, the raw materials for preparing the anti-adhesion layer further include small molecule drugs, and the small molecule drugs account for 0.05%-10% of the mass of the PLA.
[0025] Optionally, the small molecule drug is one or more of ibuprofen, naproxen, celecoxib, and aspirin.
[0026] By adding small molecule drugs to the anti-adhesion layer, these small molecule drugs have anti-inflammatory and analgesic effects, can reduce the postoperative inflammatory reaction and pain, and further promote the recovery of patients. By adjusting the proportion of the small molecule drugs in the mass of the PLA, the present application ensures the persistence and effectiveness of drug release and reduces the risk of postoperative complications.
[0027] In a second aspect, the present application provides a method for preparing an abdominal wall hernia repair composite patch, adopting the following technical solution: A method for preparing an abdominal wall hernia repair composite patch, prepared by an electrospinning process, includes the following steps: Prepare a support spinning solution, an anti-adhesion spinning solution, and an induction spinning solution for spinning the support layer, the anti-adhesion layer, and the induction layer, respectively; Spin the support layer using the support spinning solution; Spin the anti-adhesion layer on the side of the support layer using the anti-adhesion spinning solution; Spin the induction layer on the side of the support layer using the induction spinning solution, so that the anti-adhesion layer and the induction layer are located on the same side of the support layer.
[0028] The preparation process of the present application adopts electrospinning technology, which can precisely control the diameter and distribution of the fibers, thereby preparing a patch with excellent performance. By separately preparing the support spinning solution, the anti-adhesion spinning solution, and the induction spinning solution, and sequentially spinning the anti-adhesion layer and the induction layer on the support layer, the multi-layer structure construction of the patch is realized. This fine preparation process ensures the tight combination between the layers and the full play of functions.
[0029] In the above solution, the anti-adhesion layer can be spun first and then the induction layer, or the induction layer can be spun first and then the anti-adhesion layer. Therefore, the spinning order of the anti-adhesion layer and the induction layer does not affect the realization of the above composite patch structure.
[0030] Optionally, the solvents used to prepare the support spinning solution, the anti-adhesion spinning solution, and the induction spinning solution are each selected from one or more of acetone, trifluoroethanol, hexafluoroisopropanol, dimethylformamide, dichloromethane, and acetic acid.
[0031] Optionally, the solute concentration in the supporting spinning solution is 6 wt.% - 10 wt.%, the solute concentration in the anti-adhesion spinning solution is 5 wt.% - 15 wt.%, and the solute concentration in the induction spinning solution is 6 wt.% - 12 wt.%.
[0032] By adopting the above technical solutions, setting the solute concentration of the spinning solution within the above range values can ensure that the supporting material can form a stable and fibrous or membranous structure with a certain strength during the spinning process, ensuring the smooth progress of the spinning process, and at the same time not affecting their respective functions.
[0033] In summary, the present application includes at least one of the following beneficial effects: 1. After the abdominal wall hernia repair composite patch of the present application is implanted into the body, it can prevent adhesions caused by surgery, and at the same time can promote cell regeneration. The anti-adhesion layer has a unique three-dimensional pore structure, which can block the ingrowth of fibroblasts, thereby effectively reducing the occurrence of adhesions between abdominal cavity organs and the repair area after surgery; the induction layer is expected to promote the growth of peritoneal mesothelial cells, stimulate endogenous peritoneal repair, reduce patient discomfort and the occurrence of chronic inflammation. The composite stent has both the ability to prevent hernias and adhesions, and can also promote the repair and reconstruction of abdominal wall defects.
[0034] 2. By designing the unique structure of the composite patch of the present application, the anti-adhesion layer and the induction layer each play their functions without interference, and do not increase the overall thickness of the patch, reducing the foreign body sensation and discomfort of the patient when using the patch, and at the same time reducing the difficulty during the operation. Description of the Drawings
[0035] Figure 1 is a schematic diagram of the abdominal wall hernia repair composite patch according to Embodiment 1 of the present application; Figure 2 is a schematic diagram of the abdominal wall hernia repair composite patch according to Embodiment 2 of the present application; Figure 3 is a schematic diagram of the abdominal wall hernia repair composite patch according to Comparative Example 2 of the present application.
[0036] Reference numerals: 1, supporting layer; 2, anti-adhesion layer; 3, induction layer. Detailed Description of the Invention Embodiment 1
[0037] Figure 1 is a schematic diagram of the abdominal wall hernia repair composite patch according to Embodiment 1 of the present application. Refer to Figure 1, Embodiment 1 of the present application provides a composite patch for abdominal wall hernia repair, which includes: a support layer 1, an anti-adhesion layer 2, and an induction layer 3. The anti-adhesion layer 2 and the induction layer 3 are respectively arranged on the same side of the support layer 1. There are two pieces of the induction layer 3, and they are respectively located on both sides of the anti-adhesion layer 2. The minimum straight-line distance between the anti-adhesion layer 2 and the induction layer 3 is 10 mm (this size is too small, so it is not shown in Figure 1 and it can be understood that there is a tiny gap between the anti-adhesion layer 2 and the induction layer 3).
[0038] As Figure 1 shown, the structure of the support layer 1 is rectangular, with a length of 12 cm and a width of 10 cm. The length of each piece of the induction layer 3 is equal to the length of the support layer 1, and the width of each piece of the induction layer 3 is 1.2 cm, accounting for about 12% of the width of the support layer 1. The thickness of the support layer 1 is 0.45 mm, the thickness of the anti-adhesion layer 2 is 0.15 mm, and the thickness of the induction layer 3 is 0.2 mm. Therefore, from the width direction, the two end regions are slightly thicker than the middle region, but the overall thickness does not exceed 0.65 mm.
[0039] The following specifically describes the preparation method of the composite patch for abdominal wall hernia repair with the above structure, including the following steps: A. Prepare the spinning solution: Dissolve PLLA-CL with a number-average molecular weight of 80,000 in trifluoroethanol to prepare a support spinning solution with a mass fraction of 10%; dissolve PLA with a number-average molecular weight of 80,000 in dichloromethane and N,N-dimethylformamide (volume ratio of 7:3) to prepare an anti-adhesion spinning solution with a mass fraction of 9%; dissolve gelatin (biological grade) with a number-average molecular weight of 80,000 in trifluoroethanol to prepare a solution with a mass fraction of 9%, dissolve silk fibroin (purity of 90%) in formic acid to prepare a solution with a mass fraction of 12%, and mix the two according to the solute mass ratio of 3:1 (that is, the mass ratio of gelatin to silk fibroin is 3:1) to obtain the induction spinning solution; B. Spin the support layer 1: Place the support spinning solution in the syringe of a multi-nozzle electrospinning machine, control the spinning environment temperature at 25 °C, adjust the distance between the injection needle and the collecting roller to 15 cm, and control the air flow rate in the environment at 0.8 m 3 / hr; turn on the high-voltage power supply and the syringe pump, adjust the voltage to 18 kV, and the injection speed of the spinning solution is 0.002 mm / s to obtain the support layer 1 film on the rotating collecting roller; C. Spin the anti-adhesion layer 2: Place the anti-adhesion spinning solution in the syringe of a multi-nozzle electrospinning machine, control the spinning environment temperature at 25 °C, perform spinning on a specific area on the single side of the support layer 1 film obtained in step B, adjust the distance between the nozzle and the collecting roller to 15 cm, and control the air flow rate in the environment at 0.8 m 3 / hr; Turn on the high-voltage power supply and the syringe, adjust the voltage to 18 kV, the injection speed of the anti-adhesion spinning solution is 0.002 mm / s, and a double-layer film of the anti-adhesion layer 2 and the support layer 1 is obtained on the collecting rotating drum; D. Spinning the induction layer 3: Place the induction spinning solution in the syringe of the multi-nozzle electrospinning machine, control the spinning environment temperature at 25 °C, on the double-layer film obtained in step C, start spinning on a specific area approximately 10 mm adjacent to the anti-adhesion layer 2 on the single side of the support layer 1, adjust the distance between the nozzle and the collecting roller to 15 cm, and control the air flow rate in the environment at 0.8 m 3 / hr; Turn on the high-voltage power supply and the syringe, adjust the voltage to 18 kV, the injection speed of the induction spinning solution is 0.002 mm / s, and the target product, the abdominal wall hernia repair composite patch, is obtained on the collecting rotating drum. Example 2
[0040] Example 2 is basically the same as Example 1, using the same spinning solution formula and preparation process, the difference lies in their structures and shapes. Specifically, in Example 2, the induction layer 3 is in a square-within-a-square structure, and the anti-adhesion layer 2 is located inside the induction layer 3. The outer edge of the induction layer 3 is flush with the outer edge of the support layer 1, and the width difference between the inner and outer edges of the four sides of the induction layer 3 is 1.2 cm. Example 3
[0041] Example 3 is basically the same as Example 1, having the same structure and shape, the difference lies in that their spinning solution formulas are slightly different. Specifically, the formula of the anti-adhesion layer 2 in Example 3 is as follows: Dissolve PLA with a number average molecular weight of 80,000 and ibuprofen in dichloromethane and N, N-dimethylformamide (volume ratio 7:3) to prepare an anti-adhesion spinning solution with a mass fraction of 9% (including PLA and ibuprofen). Among them, ibuprofen accounts for 5% of the mass of PLA. Example 4
[0042] Example 4 is basically the same as Example 1, having the same structure and shape, the difference lies in that their spinning solution formulas are slightly different. Specifically, the formula of the induction layer 3 in Example 4 is as follows: Dissolve gelatin (biological grade) with a number average molecular weight of 80,000 in trifluoroethanol to prepare a solution with a mass fraction of 9%, dissolve hyaluronic acid (molecular weight 8 million) in formic acid to prepare a solution with a mass fraction of 12%, and mix the two in a ratio of 3:1 by solute mass (i.e., the mass ratio of gelatin to hyaluronic acid is 3:1) to obtain the induction spinning solution.
[0043] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, having the same spinning solution formula, the difference is only that in Comparative Example 1, the induction layer 3 is not set, that is, step D is missing in the preparation process.
[0044] In the spinning of the anti-adhesion layer 2 in Comparative Example 1, the spinning size is the same as that of the support layer 1. Therefore, when using the same amount of anti-adhesion spinning solution as in Example 1, the thickness of the spun anti-adhesion layer 2 is thinner than that in Example 1.
[0045] Comparative Example 2 Figure 3 is a schematic diagram of an abdominal wall hernia repair composite patch according to Comparative Example 2 of the present application. Refer to Figure 3 , Comparative Example 2 is basically the same as Example 1, with the same spinning solution formula. The only difference is that in Comparative Example 2, when performing step C, the same amount of anti-adhesion spinning solution as in Example 1 is used, and spinning is performed on all areas of one side surface of the support layer 1 film obtained in step B, that is, the size of the spun anti-adhesion layer 2 is the same as that of the support layer 1, and the spinning parameters are the same as in Example 1, obtaining a double-layer film of the anti-adhesion layer 2 and the support layer 1; when performing rectification D, the same amount of induced spinning solution as in Example 1 is used, and spinning is performed on all areas of one side surface of the anti-adhesion layer 2 of the double-layer film obtained in step C, thereby obtaining a composite patch with a sandwich structure of a support layer 1, an anti-adhesion layer 2, and an induced layer 3 from bottom to top as shown in Figure 3 .
[0046] Performance testing 1. Tensile strength First, the composite patches prepared in each example and comparative example were subjected to a tensile test using a tensile testing machine, and the tensile strength was calculated.
[0047] 2. Contact angle The contact angle of the side surface of the composite patch facing away from the support layer 1 was measured using a contact angle measuring instrument.
[0048] 3. Porosity The composite patches prepared in each example and comparative example were photographed using an optical microscope, and the pore area and the total sample area in the sample were measured by computer software, and their ratio was calculated, which is the porosity.
[0049] Table 1 Test results of tensile strength, contact angle, and porosity of the composite patch Test items Tensile strength (MPa) Contact angle (°) Porosity (%) Example 1 7.35 88.27 74.12 Example 2 7.56 83.38 80.45 Example 3 6.89 86.51 73.89 Example 4 6.17 82.15 78.63 Comparative example 1 6.87 118.23 55.38 Comparative example 2 5.31 104.42 66.54 It is not difficult to find from the test results in Table 1 that the tensile strength of the hernia repair composite patches in Examples 1-4 of the present application is generally above 5 MPa, and it can better withstand various stresses and pressures in the body and maintain the stability of the repair; the contact angle is basically not more than 90°, showing appropriate hydrophilicity, which helps to reduce adhesion to surrounding tissues; the porosity is generally above 70%, which helps to induce the ingrowth of cells and tissues and promote healing.
[0050] However, due to the lack of induction layer 3, the contact angle of Comparative Example 1 is larger than that of Example 1 and is greater than 90°, showing a certain hydrophobicity, and the porosity is also smaller than that of Example 1. The reason is that the induction layer 3 in Example 1 adopts a formula of gelatin and silk fibroin, which increases the porosity of the composite patch and also modifies the composite patch from hydrophobic to hydrophilic, which is more conducive to reducing the risk of adhesion and promoting the growth of cells and tissues.
[0051] Since the structural relationship between the anti-adhesion layer 2 and the induction layer 3 is changed in Comparative Example 2, the surface properties of the material on the side away from the support layer 1 are changed, showing a certain hydrophobicity. In addition, such a structure also makes it impossible for the anti-adhesion layer 2 to directly contact the surrounding skin when the composite patch is in use, and cannot play its anti-adhesion function. At the same time, due to such a sandwich structure, the porosity of Comparative Example 2 is lower than that of Example 1, which is not conducive to cell growth and the transmission of nutrients.
[0052] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A composite patch for abdominal wall hernia repair, characterized in that: include: A support layer (1), an anti-adhesion layer (2) and an induction layer (3), wherein the anti-adhesion layer (2) and the induction layer (3) are respectively arranged on the same side of the support layer (1), and the minimum straight-line distance between the anti-adhesion layer (2) and the induction layer (3) is 0-10 mm.
2. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The induction layer (3) is provided with two sheets, and is respectively located on both sides of the anti-adhesion layer (2).
3. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The length of each induction layer (3) is equal to the length of the support layer (1), and the width of each induction layer (3) accounts for 10%-15% of the width of the support layer (1).
4. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The induction layer (3) is a U-shaped structure, and the anti-adhesion layer (2) is located inside the induction layer (3).
5. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The outer edge of the induction layer (3) is flush with the outer edge of the support layer (1), and the width difference between the inner and outer edges of the induction layer (3) is 10%-15% of the size of the outer edge of the induction layer (3).
6. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The thickness of the support layer (1) is 0.2-0.45 mm, the thickness of the anti-adhesion layer (2) is 0.15-0.35 mm, and the thickness of the induction layer (3) is 0.1-0.25 mm.
7. The abdominal wall hernia repair composite patch according to claim 1, characterized in that: The raw materials for preparing the support layer (1) include PLLA-CL with a number average molecular weight of 80,000-110,000, the raw materials for preparing the anti-adhesion layer (2) include PLA with a number average molecular weight of 80,000-110,000, and the raw materials for preparing the induction layer (3) include one or more of gelatin, silk fibroin, and hyaluronic acid.
8. The abdominal wall hernia repair composite patch according to claim 7, characterized in that: The raw materials for preparing the anti-adhesion layer (2) also include small molecule drugs, and the small molecule drugs account for 0.05%-10% of the mass of the PLA.
9. The abdominal wall hernia repair composite patch according to claim 8, characterized in that: The small molecule drug is one or more of ibuprofen, naproxen, celecoxib, and aspirin.
10. The method for preparing the composite patch for abdominal wall hernia repair according to any one of claims 1 to 9, characterized in that: The electrospinning process is used for preparation, including the following steps: Respectively preparing a support spinning solution, an anti-adhesion spinning solution and an induction spinning solution for spinning a support layer (1), an anti-adhesion layer (2) and an induction layer (3); Spinning a support layer (1) using a support spinning solution; Using an anti-adhesion spinning solution to spin an anti-adhesion layer (2) on the side of the support layer (1); The induction layer (3) is spun on the side of the support layer (1) using an induction spinning solution, so that the anti-adhesion layer (2) and the induction layer (3) are located on the same side of the support layer (1).
Citation Information
Patent Citations
Anti-adhesion tissue repair membrane and preparation method thereof
CN104414773A
Anti-infection and anti-adhesion composite hernia repair patch and preparation method thereof
CN111714707A
Double-layer multifunctional hernia patch and preparation method thereof
CN118846245A
Multilayer ultra-light hernia patch
CN119655928A
Hernia repair piece
CN203122677U